Inhibition of the in vitro Activities of α-Amylase and Pancreatic Lipase by Aqueous Extracts of Amaranthus viridis, Solanum macrocarpon and Telfairia occidentalis Leaves - Oluwagunwa, Olayinka A.; Alashi, Adeola M.; Aluko, Rotimi E. (Frontiers in Nutrition, 2021)
Inhibition of digestive enzymes such as α-amylase and pancreatic lipase (PL) is a promising therapeutic strategy for the treatment and management of chronic health conditions such as diabetes and obesity. Therefore, the aim of this work was to determine the enzyme inhibitory activity of polyphenol-rich aqueous extracts of Amaranthus viridis (AV), Solanum macrocarpon (SM) and Telfairia occidentalis (TO), which were produced using multiple urea fertilizer doses (0-80 kg/ha) and studied at two time points (applied at planting or 2 weeks after seedling emergence). Leaf extracts were obtained using aqueous extraction (1:20, leaves:water) for 4 h at 60°C followed by centrifugation and freeze-drying of the supernatant. Results showed that the extracts inhibited α-amylase, and pancreatic lipase dose-dependently with TO extracts having significantly (p < 0.05) higher inhibitory activities for both enzymes. Fluorescence intensity and circular dichroism spectra in the presence and absence of leaf extracts indicate significant changes to the enzyme protein secondary and tertiary conformations. We conclude that the leaf extracts, especially from TO are potential agents for reducing calorie intake as a preventive or treatment tool against chronic diseases such as diabetes and obesity.